2023
DOI: 10.24095/hpcdp.43.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of adult-oriented outdoor play publications in Canada

Abstract: Introduction Since 2015, there has been growing interest in Canada and beyond on the benefits of outdoor play for physical, emotional, social and environmental health, wellbeing and development, for adults as well as children and youth. Methods This scoping review aims to answer the question, “How, and in what context, is adult-oriented outdoor play being studied in Canada?” We conducted an electronic search for peer-reviewed articles on outdoor play published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(66 reference statements)
0
2
0
Order By: Relevance
“… 6 Following its release, research focused on active play showed a tenfold increase. 9 , 10 Moreover, the document played an important role in influencing a legal decision by the BC Supreme Court regarding a playground injury case—an opportunistic lawsuit that unfairly criticized outdoor play. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Following its release, research focused on active play showed a tenfold increase. 9 , 10 Moreover, the document played an important role in influencing a legal decision by the BC Supreme Court regarding a playground injury case—an opportunistic lawsuit that unfairly criticized outdoor play. 11…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing interest in active play in public health research, 9 , 10 a globally harmonized measurement tool with established validity and reliability is currently unavailable. This gap may be due to the sporadic and spontaneous nature of active play, 12 as well as cultural and geographical variations influencing its perception and practice.…”
Section: Introductionmentioning
confidence: 99%